THE EFFECT OF FINANCIAL COMPENSATION, JOB SATISFACTION AND DISCIPLINE ON EMPLOYEE PERFORMANCE - Melkyory Andronicus; Ho Wie Sin; Stevanny Stevanny; Ayang Anggrainy (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The purpose of the research is to examine and analyze the effect of financial compensation, job satisfaction and work discipline on the performance of employees at PT. Continental Library. PT. Pustaka Benua is a company engaged in the sale of office stationery. Financial compensation has a salary discrepancy with the 2020 UMR and no health benefits, job satisfaction is still low, employee discipline at the company is still not optimal and employee performance is not optimal. The population is all employees of PT. Benua Library with a total of 64 employees and a sample of 64 employees. The research method uses multiple linear regression analysis techniques. The research reaction is financial compensation and discipline partially affecting the performance of employees at PT. Pustaka Benua. Job satisfaction partially does not affect the performance of employees at PT. Continental Library. Financial compensation, job satisfaction and discipline jointly affect the performance of employees at PT. Continental Library.